Screening, identification, and application of nucleic acid aptamers applied in food safety biosensing. (May 2022) - Liu, Ruobing; Zhang, Fuyuan; Sang, Yaxin; Katouzian, Iman; Jafari, Seid Mahdi; Wang, Xianghong; Li, Wenjing; Wang, Jine; Mohammadi, Zahra
Abstract: Background: Nucleic acid aptamers, defined as small functional nucleic acids that can selectively bind to a specific target, have become one of the main bio-recognition elements in biosensing. Aptamers can selectively bind to specific targets, such as proteins, peptides, small organic molecules as well as metal ions in food samples. Scope and approach: Aptamer-based bioassays are promising alternatives to traditional methods offering a rapid and reliable biosensing technique to detect harmful substances in food products. These functional single-stranded DNA (ssDNA) or RNA molecules are initially identified and then selected by the SELEX (systematic evolution of ligands by exponential enrichment) based on some rounds to screen the aptamer strands binding to the selected target. Next, a post-SELEX protocol is implemented to obtain the intended properties for practical applications. Key findings and conclusions: Numerous aptamers are being screened against key analytes in the food safety branch to develop a variety of biosensing techniques in this day and age. This revision enlarges upon recent advances in SELEX and post-SELEX methods for aptamers in the food safety arena. It focuses on their applications in detecting pesticides, veterinary drugs, biotoxins, allergens, foodborne pathogens, and other hazardous substances in food products. Last but not least, different techniques with aptamers are presented as highly effective methods for target detection. Graphical abstract: Image 1 Highlights: Aptamers can selectively bind to specific targets including many analytes in foods. Aptamer-based bioassays are promising alternatives to traditional methods. Aptasensors offer a rapid and reliable biosensing technique. They are selected by SELEX (systematic evolution of ligands by exponential enrichment). Next, a post-SELEX protocol is implemented to obtain intended properties in practical use.